First contribution to the study of the ants (Hymenoptera, Formicidae) of the Ζagοri region (Epirus, Greece): Αn annotated list of species - Legakis, A. (ENTOMOLOGIA HELLENICA, 1983)
The paper contains records of 33 ant species collected in the Zagori region of Northwestern Greece in 1979 and 1981. These are the first records of ants from this region. Some notes on their morphology and ecology are included. An analysis of the general distribution of the species shows that the influence of the Mediterranean, South European, Asiatic and Pontic elements is approximately equal. For some species the region is the southernmost limit in the Balkans. Seven species were observed only over l000 m. while three of them were observed only over 1400m. Most species arc either insectivores or omnivores. Omnivores and species with Mediterranean or South European distribution predominate in or near human settlements.